Effect of heat treatment on photoelectrochemical performance of hydrothermally synthesised Ag2S/ZnO nanorods arrays - Holi, Araa Mebdir; Zainal, Zulkarnain; Ayal, Asmaa Kadim; Chang, Sook Keng; Lim, Hong Ngee; Talib, Zainal Abidin; Yap, Chi Chin (Elsevier, 2018)
Low temperature hydrothermal method was used to produce a large surface area ZnO NRs on conductive glass. The same method was used to fabricate a photoelectrode of Ag2S quantum dots onto the nanorod arrays. Ag2S QDs/ZnO NRAs heterostructure was employed as photoanode in a standard 3-electrodes photoelectrochemical cell. A significant enhancement in the photoelectrochemical performance was observed for the Ag2S QDs/ZnO upon heat treatment 400 °C which displayed an impressive photoconversion efficiency of 4.08% by achieving ∼10-times higher compared to bare ZnO NRAs. This enhancement was attributed to the improved morphological structure, crystallinity and optical properties of the synthesised heterostructures.